PROBLEMS OF FORMATION OF FUNDAMENTAL SCIENTIFIC CONCEPTS - Sydykova, Zhainagul; Yerzhenbek, Bulbul; Rakhimberdina, Anargul (Pedagogy and Psychology, 2022)
The system of concepts is the basis of knowledge, all data is concentrated around them. Mastering scientific concepts contributes to a deeper and better understanding of the laws and theories of natural science, as these laws and theories reflect the interdependent relationship between scientific concepts. The high quality of students ' knowledge depends on the degree of formation of their system of concepts. The assimilation of scientific concepts by students, the ability to apply them in practice, in life occurs only with purposeful learning. The formation of scientific concepts is an active activity aimed at solving cognitive tasks. This activity includes setting and solving problems, formulating and testing hypotheses. The meanings of scientific concepts are revealed only in their system, through their relationships, which reflect the objective connections of things and phenomena. Our article describes the methodology for the formation of scientific concepts. We took the concept of energy as one of the examples of the formation of scientific concepts.